A coupled hygro-thermo-mechanical fiber beam model for reinforced concrete structures. (November 2022) - Zhang, Liuyu; Wang, Long; Mo, Di
Abstract: The mechanical behavior of reinforced concrete is affected by the environmental fluctuations of temperature and humidity. In traditional structural analysis of the using beam element, the influence of coupled hygro-thermo-mechanical effect was considered by correction coefficient terms based on data fitting of specimens, which was not very suitable for the analysis of large or complex structures. In order to catch complex behavior of reinforced concrete using beam element, a coupled hygro-thermo-mechanical fiber beam model is developed for the analysis. The model uses a sequential coupled analysis approach based on the framework of original microprestress solidification (MPS) theory and fiber beam element method, which contains important features of reinforced concrete beam such as non-uniform ageing, creep, shrinkage, thermal dilation. Several concrete beam and reinforcement concrete beam experiment data, contrasting examples between the fiber beam element model and conventional 3D solid element model and a typical example of reinforced concrete box beam on structural scale were used to verify the presented model. Overall, good results were obtained in all the tests. The results show that the MPS intrinsic creep property could predict the behavior of concrete beams well. Area weighted average temperature and average relative humidity is an efficient simplified method to catch the MPS intrinsic creep property. Fiber beam element model coupled with MPS intrinsic creep property and a finer subdivision scheme can predict the behavior of beam well under complicated conditions as well as 3D solid element model. The model developed in this study can be used for large structures efficiently.